All Days 1992
DOI: 10.2118/24592-ms
|View full text |Cite
|
Sign up to set email alerts
|

Drilling Through Highly Fractured Formations: A Problem, a Model, and a Cure

Abstract: It is usually accepted that wellbore instabilities are caused by either or both an excessive stress concentration at the borehole wall and the chemical reactivity of the formation. Assuming good hole cleaning, common cures for such instabilities are therefore mud density increase and/or change of the mud system. However, even though these methods have proved highly successfull when drilling through intact formations, the same may not stand when it comes to highly fractured rocks. The purpose of this paper is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…If the difference between mud pressure and pore pressure exceeds the threshold pressure, the synthetic-based fluids might invade the microfractures, which may reduce the internal friction angle and destabilize the wellbore (Hale et al 1992;Labenski et al 2003;Chen et al 2002;Al-Bazali et al 2005). Therefore, in stressed-shale formations, the mudweight increase would have negative consequences on wellbore stability (Santarelli et al 1992). Meanwhile, very high osmotic pressure was generated between the drilling fluid and the formation.…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…If the difference between mud pressure and pore pressure exceeds the threshold pressure, the synthetic-based fluids might invade the microfractures, which may reduce the internal friction angle and destabilize the wellbore (Hale et al 1992;Labenski et al 2003;Chen et al 2002;Al-Bazali et al 2005). Therefore, in stressed-shale formations, the mudweight increase would have negative consequences on wellbore stability (Santarelli et al 1992). Meanwhile, very high osmotic pressure was generated between the drilling fluid and the formation.…”
Section: Case Studymentioning
confidence: 99%
“…However, some field cases in the GOM, Colombia, and Canada have demonstrated that wellbore-instability problems still occurred even when oil-or synthetic-based fluids were used, especially in fractured formations (Santarelli et al 1992;Rojas et al 2006;Gallant et al 2007;Last et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have been written on this phenomenon. 9 In Norway Valhall field, this phenomenon is suspected to be one of the major causes of shale instability. Preventive measures include use of effective sealing agents for fractures, e.g.…”
Section: Shale/fluid Interaction Mechanismsmentioning
confidence: 99%
“…Obviously, the influence of natural or artificial induced fracture around the wellbore on wellbore stability cannot be ignored. Santarelli [1] (1992),Maury [2] (1994), Last [3] (1995), Mclellan [4] (1996), Zhang [5] (1999), Labenski [6] (2003), Franck [7] (2003), Chen [8,9,10,11] etc. derived the same conclusion from experiment and analysis of discrete element, Due to the existence of fissure, the seepage of drilling fluid or its filtrate along the microfracture and bedding surface will lubricate the fissure and reduce the angle of internal friction, the gradually reduced strength of formation is the fundamental reason for wellbore instability.…”
Section: Introductionmentioning
confidence: 99%